TEACHING READING PROCEDURE TEXT THROUGH CONCEPT ORIENTED READING INSTRUCTION (CORI) TO THE TENTH GRADE STUDENTS OF STATE SENIOR HIGH SCHOOL 13 PALEMBANG - Jaya, Aswadi; Marleni, Marleni (English Community Journal, 2018)
The objective of the study was to find out whether or not there were any significant different scores obtained by the students who were taught through concept-oriented reading instruction (CORI) method and those who were not. A quasi-experimental design, specifically nonequivalent control group design was applied in this study. The result of the study showed that the studentsâ scores in paired sample t-test of experimental group higher than control group (-11.83 > -12.64), while in independent sample t-test, the critical value 0.05 significance level with df 35 (36-1) was 1.697 and t-obtained 1.992. It means that tobtained was higher than t-table as critical value (1.992 > 1.697). Consequently, the alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected. It could be concluded that, teaching reading comprehension of procedure text through Concept-Oriented Reading Instruction (CORI) method to the tenth grade students of state senior high school 13 Palembang was effective